Fulvic Acid from Oil Palm Empty Fruit Bunches as Feed Additive Improves Digestive Tract and Intestinal Morphology in Broilers: Aditif Pakan Asam Fulvat Tandan Kosong Kelapa Sawit untuk Memperbaiki Saluran Pencernaan dan Morfologi Usus pada Ayam Pedaging - Dimawarnita, Firda; Dwi Margi Suci; Mugia Reksa Wicaksari; Yora Faramitha; Erwinsyah, Fayyadh Altamis; Donny Nugroho Kalbuadi; Didiek Hadjar Goenadi; Komang Gede Wiryawan; Arif Darmawan (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
The use of Antibiotic Growth Promoters (AGPs) in the poultry industry led to farmers’ dependence on antibiotics. Therefore, a safer alternative feed additive, such as fulvic acid, was needed. This study aimed to evaluate the effectiveness of fulvic acid extracted from oil palm empty fruit bunches (FA-OPEFB) as a feed additive on broiler chickens’ digestive tract and intestinal morphology. A total of 150 broiler chickens were used in a Completely Randomized Design (CRD) consisting of three treatments and five replications: P0 (drinking water without FA-OPEFB), P1 (drinking water with 0.1% FA-OPEFB), and P2 (drinking water with 0.2% FA-OPEFB). Observed variables included the relative weight and length of the digestive tract and intestinal morphology. The results showed that the addition of FA-OPEFB in drinking water significantly affected the ileum percentage, villus height, crypt depth, and villus surface area. It was concluded that 0.2% FA-OPEFB in drinking water reduced the relative weight and length of the ileum and improved intestinal morphology in broiler chickens. Key words:           broiler chicken, digestive tract, fulvic acid, intestinal morphology, OPEFB